2015
DOI: 10.1021/acsami.5b02252
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose–Zeolite Composite Films for Odor Elimination

Abstract: Free standing and strong odor-removing composite films of cellulose nanofibrils (CNF) with a high content of nanoporous zeolite adsorbents have been colloidally processed. Thermogravimetric desorption analysis (TGA) and infrared spectroscopy combined with computational simulations showed that commercially available silicalite-1 and ZSM-5 have a high affinity and uptake of volatile odors like ethanethiol and propanethiol, also in the presence of water. The simulations showed that propanethiol has a higher affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 39 publications
(84 reference statements)
4
24
0
Order By: Relevance
“…CNFs have been shown to enable the structuring of particles [e.g., zeolites (27), metal-organic frameworks (28), and TiO 2 (29)], and here, we demonstrate the universal application of CNF to induce cohesion in particle constructs even if incorporated at extremely low fractions. We show that the ability of CNF to form a topologically complex network with high supramolecular cohesion is linked to the high aspect ratio of the fibrils (nanometers wide and up to several micrometers long; Fig.…”
Section: Introductionsupporting
confidence: 53%
“…CNFs have been shown to enable the structuring of particles [e.g., zeolites (27), metal-organic frameworks (28), and TiO 2 (29)], and here, we demonstrate the universal application of CNF to induce cohesion in particle constructs even if incorporated at extremely low fractions. We show that the ability of CNF to form a topologically complex network with high supramolecular cohesion is linked to the high aspect ratio of the fibrils (nanometers wide and up to several micrometers long; Fig.…”
Section: Introductionsupporting
confidence: 53%
“…A recent study by Keshavarzi et al [32] regarding composite material showed a similar morphology with NcMMT. In their study, composite (CNF-composite) was produced by sonicating the dispersions of cellulose nanofibrils (CNF) and zeolite.…”
Section: Characterization Of Mmt Ncc and Ncmmtmentioning
confidence: 56%
“…136,137 In odor control, they have been widely used in applications such as agricultural and municipal wastes, as well as in pet litter, 138,139 applied as topical agents to control body odor, 140 and combined in cellulosic films for food packaging. 141 Zeolites have been incorporated into cotton and polyester fabrics with the potential to provide protection against radiation. [142][143][144] Odor control using zeolite technology by Sciessent Lava TM has multiple textile applications, including apparel, sporting equipment, linens, and pet products, 145 with laundering regenerating the zeolite adsorption capacity.…”
Section: Odor Control Through Adsorptionmentioning
confidence: 99%